Necessary understandings about international adoptions - Garcia Escobar, Jorge (2009)
In the field of the Social Work in the promotion of the infancy and adolescence the topic of international adoptions emerges as one of the preferred and currently valued alternatives to achieve the fulfillment of the rights of the children, girls and teenagers abandoned or subject to the flagrant violation of their rights. Among the communities where the occurrence of abandonment and threat to life of children, girls and teenagers take place, there is the idea that the best solution would be to give in adoption the infants and teenagers victimized to other families with better moral and material capacities. Among professional social workers the debate is between those who consider adoptions as prioritary and necessary, and those who think that all efforts should be exhausted so that the children and teenagers do not lose their family of origin or natural network